Inflammation and Pancreatic Ductal Adenocarcinoma: A Potential Scenario for Novel Drug Targets - Uomo, Ilaria; Miraglia, Simona; Pastorello, Maurizio (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Mechanism of NF-κB action (Author: Boghog2 from Wikimedia Commons)